Assessing the Level of Effectiveness of Marketing Activities of HEIs in the National Capital Region - Mercado, J; Mercado, M A V (KnE Social Sciences, 2018)
Higher Education Institutions in the Philippines, just as any business institutions, conduct marketing activities to ensure the thriving admission and retention of students. This paper ascertained the effectiveness of the marketing activities used by selected HEIs in the National Capital Region through the “Four P’s of Marketing”. Results of the study can be used as references by HEIs in updating their marketing activities. Keywords: Marketing Activities, Four Ps of Marketing, Higher Education Institution